PSYCHOSOMATICS OF GASTRITIS - Juraeva Dildora Nasirdinovna; Sunnatillaeva Umida Rovshanovna (Modern American Journals, 2025)
The article examines the influence of psychoemotional factors on the development and course of gastritis. The relationship between stress, anxiety, suppressed emotions and disorders in the gastrointestinal tract is analyzed. The mechanisms of psychosomatic effects are considered, including the effect of stress on gastric juice production, gastric motility and microflora.
Keywords: Psychosomatics, gastritis, stress, emotional stress, Helicobacter pylori, gastrointestinal tract, psychoemotional factors, neuroendocrine regulation, autonomic nervous system, cognitive behavioral therapy, psychosomatic disorders